Sequence analysis of MIPS-1s gene isolated from the low-phyticacid inbred line of maize Qi319 and characterization of its expression patterns - Gao, Qinghua; Zhang, Cui; Fan, Wei; Niu, Dongdong; Rong, Ruijuan; Li, Xuejiao; Miao, Liuyang; Liu, Lijuan; Liu, Guozhen (The Indian Journal of Genetics and Plant Breeding, 2016)
Myo-inositol 1-phosphate synthase (MIPS) is a pivotal enzyme that initiates the first step of phytic acid synthesis. In the present study the MIPS-1s gene isolated was from an inbred line of maize Qi319 containing low contents of phytic acid (lpa). Its sequence and expression patterns were also characterized. Results showed that the full-length genomic DNA sequence of the MIPS-1s gene is comprised of ten exons and nine introns, with a length of 3596 bp, and an open reading frame of 1533 bp that encodes a protein with 510 amino acids. A single amino acid substitution was found, compared to the sequence of the inbred maize line B73. In silico promoter analysis revealed various ciselements that might contribute to the differential regulation of MIPS-1s. The expression patterns of MIPS-1s proteins in leaves, roots, flowers and developing seeds of maize were also investigated using western blot. It showed similar patterns compared to the control line (Chang 7-2), suggesting that the MIPS-1s protein plays similar roles in the process of maize development and growth. Notably, it was found that the control line had a dramatically higher abundance of MIPS-1s protein than did Qi319, in the developing seeds and especially during the early period. This strongly indicates that higher levels of MIPS expression should precede and/or accompany synthesis and accumulation of phytate